Pronunciation Instruction and Students' Practice to Develop Their Confidence in EFL Oral Skills - Ana Cristina Tlazalo Tejeda; Nora M. Basurto Santos (Universidad Nacional de Colombia, 2014)
The aim of this article is to inform on research intended to find out how pronunciation instruction of English as a foreign language was handled in the language classroom with elementary students and also understand if pronunciation instruction had an impact on students' confidence when using it. In order to do this, a qualitative case study was carried out with learners of elementary English as a foreign language at the Language School of Universidad Veracruzana, Mexico. Class observation, a written text, and semi-structured interviews comprised the data collection instruments. The findings showed that not only teacher pronunciation instruction is necessary when learning English as a foreign language but that a lot of student practice is key to developing and enhancing learners' pronunciation as well.